Extended Half-life rFVIII for the Treatment of Hemophilia A: Drugs Consumption and Patients’ Perspective - Roggeri, Daniela Paola; Zanon, Ezio; Biasoli, Chiara; Roggeri, Alessandro (Farmeconomia. Health Economics and Therapeutic Pathways, 2020)
Prophylaxis is recognized as the most effective treatment regimen for patients with severe hemophilia A. Prophylaxis with standard half-life (SHL) FVIII products requires frequent intravenous administrations, at least two-three times per week. Frequency of injections is reported as one of the major obstacles to adherence to treatment and caused impairment in quality of life (QoL) and possible clinical implications. The extended half-life (EHL) rFVIII products recently reimbursed by Italian National Health Service (NHS), give the possibility of prophylactic dosage regimens characterized by reduced administration frequency with the potential to increase adherence to therapy and to improve QoL and clinical outcomes. Based on the approved dosing regimens the minimum and maximum number of administrations per year and the annual consumption for the marketed EHL rFVIII products were estimated. Compared to Adynovi® and Elocta®, Jivi® is the drug associated with the lowest number of administrations per year while versus Esperoct® is associated to a slightly higher maximum number of administrations per year. Furthermore, Jivi® has an annual mean consumption per kg lower than Adynovi®, Elocta® and Esperoct® (-24%, -27% and -22%, respectively). The contemporary reduction of number of injections per year and the lower annual mean consumption (IU) represent important benefits for the patient. From the economic point of view, at the prices published in Italian Official Journal, Jivi® weighted average annual expenditure per patient is 26% lower than Adynovi® and 29% lower than Elocta® and a saving is possible even considering a 10% increase in Jivi®’s price per IU versus comparators. Among the EHL rFVIII concentrates Jivi® appears to be more suitable to cover patients’ needs due to the possibility to adopt different dosage regimens (up to every 7 days) and is associated with the lowest average annual consumption per patient allowing a more predictable budget forecast and overall reducing the NHS expenditure.